Analisis Proses Rekrutmen dan Seleksi Crew Kapal PT. Pulau Seroja Jaya Cabang Banjarmasin - Indriyani, Indriyani; Rayendra, Altril; Saputro, Eko Yusuf (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2024)
PT. Seroja Jaya Island carries out recruitment and selection of prospective workers who will be used in operating its ships so that they can work well and responsibly in accordance with the company's goals. This research aims to determine the recruitment process for ship crews belonging to PT Pulau Seroja Jaya Banjarmasin Branch. In carrying out the operations of its fleet of ships, PT. Seroja Jaya Island Banjarmasin Branch certainly requires a process of recruiting new crew and replacing ship crew professionally and in accordance with existing regulations. In this research, data collection was carried out using observation, literature study and interviews, while the data analysis method used was descriptive qualitative. The results of this research show that the ship crew recruitment process at PT. Seroja Jaya Island Banjarmasin Branch has been carried out in accordance with predetermined procedures. Terms and/or ship crew recruitment process carried out by PT. Seroja Jaya Island Banjarmasin Branch begins with submitting prospective ship crew members to ratifying the transfer order, sea work agreement and ship crew certificate by the crewing department or company. The recruitment process must be adjusted between the abilities and competencies of job applicants and the company's needs, so that in the future no jobs will be occupied by people whose abilities and skills do not suit them. Obstacles faced in the recruitment process include incomplete applicant certificates and certificates that have expired, thus hampering the administrative selection or filing process and certificates that have expired, thus hampering the administrative selection or filing process.